(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The rich scientific heritage of Central Asian thinkers and scholars is recognized throughout the world not only for the development of science in the region, but also for the development of world civilization. In particular, the results of the works of Ibn Sina, Beruni, al-Khwarizmi, Farobi and other thinkers have been serving the world’s scientists for centuries. The issues of extensive use of this scientific heritage in the upbringing of a harmoniously developed generation are reflected in this article, and the author addresses the culture of the first and second Renaissance in Central Asia. The article also reflects the large-scale reforms being carried out in Uzbekistan today in relation to the upbringing of the younger generation.